Critical Representation of Figures, Symbols, and Power in Political Communication: Bibliometric Analysis of Phenomenological Studies - Anida Kusuma Ning Ariati; Anang Sujoko (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The representation of political figures, symbols, and power in contemporary political communication has become increasingly complex as digital media expand and political narratives evolve. However, a comprehensive understanding of how these issues have been examined within phenomenological political communication studies remains limited. Therefore, this study aimed to investigate the critical representation of figures, symbols, and power in political communication through a critical phenomenological perspective integrated with bibliometric analysis. The research employed a bibliometric approach combined with critical phenomenology to map publication trends, influential authors, dominant keywords, and citation networks in phenomenological studies of political communication published between 2010 and 2025. Data were collected using Publish or Perish software and analyzed with Microsoft Excel and VOSviewer to visualize relationships among authors, keywords, and citations. The findings revealed a substantial increase in publications since 2021, indicating growing scholarly interest in the field. The dominant themes identified included gender representation, populist political figures, identity politics, and the symbolism of power in digital communication environments. The analysis further demonstrated that scholarly discourse has become increasingly fragmented while simultaneously consolidating around several influential clusters, particularly those related to communicative action, political narratives, and symbolic representation. The study concludes that integrating bibliometric methods with critical phenomenology effectively uncovers the discursive landscape, intellectual structure, and representational biases in contemporary political communication research. These findings advance political communication studies conceptually and methodologically by strengthening critical perspectives on representation, symbolic experience, and power relations in political discourse.